2020
DOI: 10.1186/s13065-020-00701-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Cu(II) and Co(II) porphyrins: role of ligand modification

Abstract: In this study, we report antibacterial activity of metalloporphyrins; 5, 10, 15, 20-tetrakis (para-X phenyl)porphyrinato M (II) [where X = H, NH 2 and COOMe for M = Cu and X = COOH and OMe for M = Co]. The activity study of the assynthesized metalloporphyrins toward two Gram-positive (S. aureus and S. pyogenes) and two Gram-negative (E. coli and K. pneumoniae) bacteria showed a promising inhibitory activity. Among the complexes under study, the highest antibacterial activity is observed for 5, 10, 15, 20-tetra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…The antibacterial efficacy and required GaPPIX concentration will strongly depend on the particular wound infection scenario, and underlying effects need to be further investigated and considered for future medical application of GaPPIX-functionalized materials. Nevertheless, GaPPIX is a promising alternative to current antibiotics and will, without a doubt, be investigated in future studies along with other metal complexes. , Interestingly, Beyene and Wassie investigated the antibacterial effect of copper (Cu) or cobalt (Co) that was complexed within porphyrin rings containing different substitutes than the protoporphyrin ring . It was shown that porphyrin rings bearing carboxylic acid groups had increased antibacterial efficacy compared to other substitutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial efficacy and required GaPPIX concentration will strongly depend on the particular wound infection scenario, and underlying effects need to be further investigated and considered for future medical application of GaPPIX-functionalized materials. Nevertheless, GaPPIX is a promising alternative to current antibiotics and will, without a doubt, be investigated in future studies along with other metal complexes. , Interestingly, Beyene and Wassie investigated the antibacterial effect of copper (Cu) or cobalt (Co) that was complexed within porphyrin rings containing different substitutes than the protoporphyrin ring . It was shown that porphyrin rings bearing carboxylic acid groups had increased antibacterial efficacy compared to other substitutes.…”
Section: Resultsmentioning
confidence: 99%
“…44,47 Interestingly, Beyene and Wassie investigated the antibacterial effect of copper (Cu) or cobalt (Co) that was complexed within porphyrin rings containing different substitutes than the protoporphyrin ring. 48 It was shown that porphyrin rings bearing carboxylic acid groups had increased antibacterial efficacy compared to other substitutes. The authors concluded that this might be due to an enhanced lipophilicity of the compound and thus enhanced uptake through the bacterial membranes.…”
Section: Methodsmentioning
confidence: 99%
“…As an essential trace element in the human body, Cu can promote bone regeneration and antibacterial activity [ [16] , [17] , [18] ]; thus, it is an ideal material for prosthesis modification. However, a large release of Cu ions can cause tissue damage [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt metalloporphyrin complexes have been extensively investigated since the early sixties, firstly as biomimetic models of hemoproteins, especially of vitamin B 12 [1][2][3]. These coordination compounds are indeed explored in many domains, such as catalysts [4], gas detection [5], biological activities, antifungal and antibacterial [6,7], building blocks [8,9], photovoltaic cells [10][11][12], and sensors [13,14]. Organic dyes are used in many industrial applications: paper, cosmetics, but especially in the food, textile, pharmaceutical, and medical diagnostic industries [15,16].…”
Section: Introductionmentioning
confidence: 99%